Intra- and inter-generic transfer of pathogenicity island-encoded virulence genes by cos phages - Chen, John (ISME J, 2015)
Bacteriophage-mediated horizontal gene transfer is one of the primary driving forces of bacterial evolution. The pac-type phages are generally thought to facilitate most of the phage-mediated gene transfer between closely related bacteria, including that of mobile genetic elements-encoded virulence genes. In this study, we report that staphylococcal cos-type phages transferred the Staphylococcus aureus pathogenicity island SaPIbov5 to non-aureus staphylococcal species and also to different genera. Our results describe the first intra- and intergeneric transfer of a pathogenicity island by a cos phage, and highlight a gene transfer mechanism that may have important implications for pathogen evolution.